Jawi Field in Elementary School Islamic Education Curriculum: One Analysis of Literature: Bidang Jawi dalam Kurikulum Pendidikan Islam Sekolah Rendah: Satu Analisis Literatur - Tamyis, Mohd Mazhan; Suppian, Zahari; Che Md. Ghazali, Nor Hasnida (Jurnal Pendidikan Bitara UPSI, 2021)
Jawi scripts is one of the cultural heritage that is closely related to the identity of the community, national identity and has its own historical value. The importance of elevating Jawi writing has been guided through the implementation of Jawi in the Primary School Standard Curriculum (KSSR) of Islamic Education (BJdKPI) Revision 2017. However, the existence of significant gaps between curriculum planning at the central level and the reality of teacher implementation in the classroom needs to be addressed. This paper discusses the results of a literature analysis that covers the study of the field of Jawi in three main scopes, namely (1) the development of Jawi, (2) the teaching and learning of Jawi, and (3) the mastery of Jawi. This conceptual paper aims to identify the focus of research, topics and issues related to the field of Jawi in the Islamic education curriculum. The methodology of this study uses the literature highlight approach by content analysis as well as narrative analysis. Search selected journals based on the year of publication from 2016-2021 using the Google Scholar search medium. Based on the theme of ’Jawi field’, the findings of the study after the screening showed that there were 13 articles from selected journals related to the field of study since 2016 until now. The results of the analysis showed four main elements of the discussion in the previous study, namely (1) the relevance of Jawi in the Islamic Education curriculum, (2) students’ achievement and interest in Jawi, (3) effective Jawi teaching, and (4) Islamic education teachers as curriculum change agents. The implementation of Jawi in the primary school Islamic education curriculum faces great challenges to ensure that it continues to be dignified, especially by teachers in the classroom. The results of this study provide space for further research to evaluate the implementation of teaching and learning of Jawi at the primary school level comprehensively. Further research is also expected to provide input on suggestions for improving the implementation of the field of Jawi in the Islamic education curriculum in the future.